LAYANAN BIMBINGAN DAN KONSELING SOSIAL UNTUK MENCEGAH DAN MEREDUKSI KECENDERUNGAN PERILAKU PHUBBING - Agung Gumilar, - (2023)
Along with the times, human life from time to time continues to experience changes such as how to dress, how to work, how to communicate, etc. The industrial revolution 4.0 with the concept of using high-technology and society 5.0 with the concept of a super smart society, these two concepts have had an impact on the phenomenon of excessive use of technology. Phubbing behavior is a consequence of the times, where a person prefers activities in the virtual world rather than interacting with the others in the real world. Phubbing behavior has the potential to hinder the developmental tasks of students at school so that the purpose of this study is to provide an overview of phubbing behavior tendencies and to formulate social guidance and counseling services that can be implemented to overcome phubbing behavior. This study uses a descriptive method through a quantitative approach. The participants of this study were class XI students of Tasikmalaya city high-school with a sample of 3872 people. The instrument used is the Generic Scale Of Phubbing (GSP) with a choice of answers on a scale of 1-7. The results of this study show that 97.4% of students engage in phubbing behavior. The highest level of scale based on gender is in the male group, based on school is the SMAN 10 Tasikmalaya City, based on specialization is the social studies group, and based on the duration of smartphone use is the >20 hour. This research also produces social guidance and counseling services that can implement guidance and counseling teachers in schools.